Development and Validation of a New Tool for Evaluating Educational Videos Discussing Skin Surgical Procedure Techniques - Almuqarrab FJ; Alfurayh N; AlGhamdi K (Dove Medical Press, 2024)
Fatimah J Almuqarrab,1 Nuha Alfurayh,2 Khalid AlGhamdi1,3 1Department of Dermatology, King Saud University Medical City, King Saud University, Riyadh, Saudi Arabia; 2Division of dermatology, Imam Abdulrahman Alfaisal Hospital, Ministry of Health, Riyadh, Saudi Arabia; 3Vitiligo Research Chair, Dermatology Department, College of Medicine, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Khalid AlGhamdi, Vitiligo Research Chair, Department of Dermatology, College of Medicine, King Saud University, Riyadh, Saudi Arabia, Email kmgderm@gmail.com Fatimah J Almuqarrab, Department of Dermatology, King Saud University Medical City, King Saud University, Riyadh, Saudi Arabia, Email fatimah.muq12@gmail.comBackground: The available tools for evaluating scientific content target written scientific evidence and referencing without considering surgical, technical, or video graphic aspects.Objective: This study developed and validated a tool for qualitatively evaluating videos in the field of skin surgery. This will increase the quality of recorded surgical materials published online and ultimately enhance the reliability of streaming platforms as educational resources.Methodology: Tool development included several stages: draft generation, expert panel setting, internal reliability testing, and pilot study.Results: After two rounds of expert panels evaluating the developed tool, 23 relevant items evaluating the educational value, scientific accuracy, and clarity of the surgical technical steps of the videos were obtained. We applied the tool to the top 25 YouTube videos discussing elliptical excision. Internal consistency, reliability, and substantial agreement between the raters were identified. We identified a strong positive correlation between our tool score and the global rating score (r= 0.55, P= 0.004).Conclusion: It is critical to avoid relying on any video for educational purposes. The tool generated and validated in our study can determine a video's value. A pilot study of 25 YouTube videos demonstrated that the available videos are of fair-good quality, thus necessitating the need for high-quality video production.Keywords: youtube videos, skin surgery, education, tool validation, video evaluation